FOSTER-KENNEDY SYNDROME: WHAT FUNDUSCOPY WON’T MISS: Poster Presentation - Case Report - General practitioner - Putri Nabillah Mulya; Cut Putri Samira (Ophthalmologica Indonesiana, 2024)
Abstract Introduction : Optic nerve is the only visible extension of central nervous system and often represents several intracranial diseases. This case demonstrates the importance of funduscopy in detecting intracranial mass. Case Illustration : A 45-year-old woman suffered progressive blurry vision in both eyes for a year and severe headaches and seizures. The right eye (RE) had no light perception, and the left eye (LE) had 6/60 visual acuity. The relative afferent pupillary defect (RAPD) was positive on the RE. A funduscopic examination revealed a pallor optic disc on the RE and papilledema on the LE, consistent with type 1 Foster- Kennedy Syndrome (FKS). A Head CT scan showed a 5.3x6x5 cm mass in the right frontotemporal lobe. We referred the patient to the neurology and neurosurgery department for further management and surgical intervention. Discussion : FKS is a condition associated with tumors in the frontal lobe, characterized by ipsilateral optic disc atrophy due to direct compression, contralateral papilledema due to increased intracranial pressure, and ipsilateral anosmia in advanced stages. RAPD is a sluggish pupillary response to light stimuli due to unilateral retinal or optic nerve disease that occurs anterior to the lateral geniculate body. True FKS is extremely rare nowadays because of advances in neuroimaging to detect intracranial masses earlier. Conclusion : As a primary care physician, performing a direct funduscopy on patients complaining of decreased vision, headaches, and impaired mental status is essential. Although rare, FKS should be kept in mind while finding a patient with optic disc atrophy and papilledema.